How the Computer went to School Australian Government Policies for Computers in Schools, 1983-2013 - Beale, Denise (Education, 2014)
For more than 30 years, certain governments, individuals and organisations have actively promoted computers as learning technologies. Enormous amounts of money and time have been spent promoting specific kinds of educational computing, and policies by which these might be implemented. The view that computers can enhance student learning has gained broad acceptance. The computers should not automatically be associated with success in schools. The view that all school children will benefit equally from access to computers overlooks inequities associated with differing patterns of use. How the Computer Went to School gives an account of the origins and development of the computer industry in the United States and shows how these influenced educational computing in both the US and Australia. It explores government policy that prioritises the economic benefits of educational computing for the nation and questions the proper role of the computer in education more generally.